Reglas administrativas. Examen respecto a su alcance jurídico - Margáin Manautou, Emilio (UNIVERSIDAD DE SONORA, 2018)
This document analyzes the legal scope of the administrative rule in Mexico, by contrasting the theoretical aspect of the concept with the provisions of federal legislation in light of the interpretation made by the Judicial Power.